Senin Bersinar Tasmi’ Al-Qur’an Program (Living Al-Qur’an Study at MAN 2 Sleman, Yogyakarta) - Kamal Mukhtar; Khodijatul Kubro; Muhammad Aufal Minan (Jurnal Pendidikan Agama Islam, 2023)
The living Al-Qur’an study examines various social events related to the existence of Al-Qur’an in society. At MAN 2 Sleman, there is a living Al-Qur’an study in the form of the Senin Bersinar Tasmi’ Al-Qur’an program. Purpose – This study aims to find meanings of practice Senin Bersinar Tasmi’ Al-Qur’an program with find out the “because motive” and “in order to motive” of Senin Bersinar Tasmi’ Al-Qur’an program for academic community of MAN 2 Sleman. Design/methods/approach – This research is a qualitative research with a field research pattern, descriptive and phenomenological approach. Data collection techniques using literature studies, observation, interviews, and documentation. Respondents consisted of 40 students and 10 teachers. The data is then analyzed through an interactive process and tested for validity by data triangulation. Findings – (1) “Because motive” of this program is awareness of obeying religious obligations and running school programs, low Al-Qur’an literacy skills, low interest in reading and memorizing Al-Qur’an, poor quality of memorization, and lack of supporting factors in learning to read and memorize Al-Qur’an, (2) “to order to motive” of this program is to become a momentum and a means to get closer to Allah Swt., get blessings, raise motivation to read and memorize Al-Quran, improve the quality of memorization, increase intelligence and discipline, training courage and strengthen ties of friendship. Originality/value – Living Al-Qur’an with the tasmi’ method for the academic community of MAN 2 Sleman needs to be improved and developed to increase abilities and motivation in getting closer to Allah Swt.